2a+9=11+7(a-1)

Simple and best practice solution for 2a+9=11+7(a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+9=11+7(a-1) equation:


Simplifying
2a + 9 = 11 + 7(a + -1)

Reorder the terms:
9 + 2a = 11 + 7(a + -1)

Reorder the terms:
9 + 2a = 11 + 7(-1 + a)
9 + 2a = 11 + (-1 * 7 + a * 7)
9 + 2a = 11 + (-7 + 7a)

Combine like terms: 11 + -7 = 4
9 + 2a = 4 + 7a

Solving
9 + 2a = 4 + 7a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7a' to each side of the equation.
9 + 2a + -7a = 4 + 7a + -7a

Combine like terms: 2a + -7a = -5a
9 + -5a = 4 + 7a + -7a

Combine like terms: 7a + -7a = 0
9 + -5a = 4 + 0
9 + -5a = 4

Add '-9' to each side of the equation.
9 + -9 + -5a = 4 + -9

Combine like terms: 9 + -9 = 0
0 + -5a = 4 + -9
-5a = 4 + -9

Combine like terms: 4 + -9 = -5
-5a = -5

Divide each side by '-5'.
a = 1

Simplifying
a = 1

See similar equations:

| 9k-8k+4k-3k+k=18 | | x/3=87 | | 4+3(1+i)=4i+6 | | 5f-2=33 | | 6p+p+2p=9 | | 18(11/63) | | 6v-5v=8 | | 19b-18b=12 | | 17a-14a=9 | | 15c-14c=5 | | x=12000-820y | | 0.09xX=127.53 | | 400+300x=300+250x | | 3h+2=5h-10 | | 2(15)-10=5+.5(15) | | -3x/7=7/8 | | 52-x^2=-4 | | 9(g-930)=522 | | 986=17(t+11) | | 4(3x+2)=-8x+8 | | 7/5=10.5/? | | 4(3x+2)=1x+11 | | H(t)=-16t^2+12t+10 | | 18-9v=-15 | | 5(5x+8)=17(4x-28) | | 4(3x+2)=5x+1 | | 3a^2+b^2=7a^2 | | 4(3x+2)=11x+1 | | 4(3x+2)=-11x+1 | | 4(3x+2)=-1x+1 | | 12x^-3y^5z^7/4x^-2y^4z^6 | | 3.5v+8=735v-4 |

Equations solver categories